Students’ Mathematical Connection Ability viewed from Self-Efficacy in Statistics - Antariksa, Kasih Ayu Dian Antariksa; Kartono, Kartono; Sukestiyarno, Sukestiyarno (Jurnal Pendidikan MIPA, 2022)
This research is a qualitative research. The purpose of this study is to describe students' mathematical connection abilities in terms of self-efficacy. Data collection techniques in qualitative research include (1) questionnaires, (2) interviews, and (3) documentation of students' work as supporting data for analysis. Data analysis in qualitative research includes data reduction, data presentation, and drawing conclusions. From this study it can be concluded that students with high self-efficacy are able to relate the 3 indicators of mathematical connection ability well, which means students with high self-efficacy will also have high mathematical connection ability. Students with moderate self-efficacy are only able to connect 2 indicators of mathematical connection ability well because students tend not to because these students lack understanding of the concepts being taught and students with low self-efficacy are only able to relate 1 indicator of mathematical connection ability well because students are less able connecting mathematical concepts. Likewise, student self-efficacy is still in the low category, this is because students still seem hesitant in working on a problem. Keywords: mathematical connection ability, self-efficacy, junior high school students. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1862-1875